The first-year analysis of the k-12 program using the UPCAT scores and UPG as a determinant for academic performance - Bass, David Franco B.; Quimbo, Philippe Joseph; Epetia, Ma. Christina F. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
The K-12 program is a twelve-year educational curriculum that is divided into six years of primary schooling, four years of junior high school and two years of senior high school. This new academic program hopes to prepare graduates to acquire mid-level skills that will provide them more opportunities in the job market even without a college degree. This study aims to determine the effect of the K-12 program to the students’ academic performance through the University of the Philippines College Admission Test (UPCAT) and the University Predicted Grade (UPG). By conducting Multivariate Ordinary Least Squares (OLS) on the average UPCAT score and its different subtests, the researchers are able to distinguish the performance of students who graduated from the K-12 curriculum, and those from the basic education curriculum. The results obtained show that graduates of the K-12 curriculum performed poorly, in all subtests of the UPCAT, compared to those who graduated from the old basic education curriculum.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: K-12 (Education).; Academic performance